Hybrid neuroelectronics: towards a solution-centric way of thinking about complex problems in neurostimulation tools - Drakopoulou, Sofia; Varkevisser, Francesc; Sohail, Linta; Aqamolaei, Masoumeh; Costa, Tiago L.; Spyropoulos, George D. (Frontiers in Electronics, 2023)
Responsive neuromodulation is increasingly being used to treat patients with neuropsychiatric diseases. Yet, inefficient bridges between traditional and new materials and technological innovations impede advancements in neurostimulation tools. Signaling in the brain is accomplished predominantly by ion flux rather than the movement of electrons. However, the status quo for the acquisition of neural signals is using materials, such as noble metals, that can only interact with electrons. As a result, ions accumulate at the biotic/abiotic interface creating a double-layer capacitance that increases impedance and negatively impacts the efficiency of neural interrogation. Alternative materials, such as conducting polymers, allow ion penetration in the matrix creating a volumetric capacitor (two orders of magnitude larger than an area-dependent capacitor) that lowers impedance and increases spatiotemporal resolution of recording/stimulation. On the other hand, the increased development and integration capabilities of CMOS-based back-end electronics has enabled the creation of increasingly powerful and energy-efficient microchips. These include stimulation and recording systems on chip (SoC) with up to tens of thousands of channels, with fully integrated circuitry for stimulation, signal conditioning, digitation, wireless power and data telemetry, and on-chip signal processing. Here, we aim to accumulate knowledge of the best component for each building block and try to strengthen the vision that bridges the gap among various materials and technologies in an effort to advance neurostimulation tools and promote a solution-centric way of thinking about their complex problems.